The problems use and protection of agricultural land in modern conditions - Bavrovska, N.; Boryshkevych, O. (Land Management, Cadastre and Land Monitoring, 2017)
Land is the fundamental national wealth under special state protection. It is believed that the efficiency of land use is the main indicator of the development of society and the state as a whole. Article 5 of the Land code of Ukraine defines ensuring rational use and protection of land the principle of land legislation. A study of the use and protection of land resources, analysis of specific measures of protection of land resources and soils is always relevant and is of interest to companies and scientists. Because the system of land use is in critical condition, the complexity and diversity of issues related to the implementation of the principles for sustainable land management in practice, necessitates further research. The purpose of this article analyzes the current state of use of agricultural lands in Ukraine and the definition of priority actions whose implementation will contribute to improving the efficiency of agricultural land use, the protection and rational use of agricultural land. Ukraine is one of Europe’s largest countries, covering an area of almost 6% in Europe, and agricultural land account for about 19% of European, including arable land - nearly 27%. In the structure of agricultural land arable land occupies 78.1 per cent, which is significantly more than in the European countries and the USA. All this is evidence of the high level of development and the load on agricultural soil cover, increases the likelihood of proliferation threats of erosion processes and degradation of the land Fund of the country As of 01.01.2016 g in Ukraine, the largest share belongs to agricultural land 42.7 million ha or 70.8 per cent, the second place is occupied by forests and forest lands is 10.6 million ha, or 17.6 percent, the third – the territory is covered by water bodies is 2.4 million ha or 4.0 %. Agrarian reform in Ukraine has led to significant changes in agriculture, in particular it partly influenced the structure of agricultural lands. The territory of Ukraine is characterized by extremely high rate of agricultural development that significantly exceeds the environmentally sound limits. In comparison with European countries, arable land can reach 30-32% of the total area, the destruction of the Ukrainian lands - 53.9 per cent Currently, there is a steady tendency of deterioration of qualitative condition of soils, in particular decreasing reserves of humus, the nutrient content of the ongoing processes of acidification, salinization and erosion, leading to degradation and desertification of the soil cover. In a market environment an important principle of land use is the economic feasibility of their involvement in the production, which is characterized by the return on the cost of cultivation of agricultural crops. The main factors of increase of efficiency of land use in agriculture are: productivity of agricultural production; farming system; the fertility of the earth. Economic efficiency of use of agricultural land in Ukraine is characterized by positive dynamics. So, slowly rising, gross output, crop yields, gross collection Crop yields tends to increase: in fruit and berry crops by 123 %, the yield of sugar beet increased by 72 %, and grain and leguminous crops by 24% in comparison with 1990. The size of the gross harvest of agricultural products, in physical terms showed a significant decrease in the level of land resources use in Ukraine. So, the gross harvest of sugar beet in 2015 decreased by 65% compared to 1990. But other crops held positive dynamics – the increase in gross collection on 12850,3 thousand tons of grain and leguminous crops and 7563 thousand tons of sunflower. In the conditions of market economy the state should use the instruments of adjustment trends in the use of resources in agriculture for the benefit of national interests, but it does not blow up The basis of formation of effective usage of agricultural lands, in addition to allocated land legislation, there should be organizational-economic and land-legal principles: the unity of political, economic, environmental and technological approaches to agricultural land use; a comprehensive solution to issues of effective use of land and other natural resources; accounting for zonal differences in the placement and use of land resources for agricultural purposes; consideration of multifunctionality of land in agriculture; priority agriculture land. Keywords: agricultural land, farmlands, land protection, rational land use.